TINJAUAN HUKUM ISLAM MENGENAI TENAGA KERJA WANITA (TKW) DI LUAR NEGERI DALAM MENINGKATKAN PENDAPATAN KELUARGA - Mar’atus Soleha; Irvan Iswandi; Ali Aminulloh (Melati Institute, 2023)
Law family income makes women take independent role in earning family income by working abroad to create family harmony in Islamic law. The purpose of the present study was to determine the perspective of Islamic law on female workers abroad and their role in increasing family income. The present study used types were field research with qualitative research approach and qualitative descriptive research. The data sources of the study were primary and secondary data sources. The sampling method was sampling purposive. It used observation, semi-structured interview and documentation research methods. The research results showed that; 1) The family income increased after working abroad. By working abroad, they were able to improve their family’s quality of life, pay their children’s education, build comfortable homes, and have savings in the form of money or assets; 2) Women who worked abroad to increase family income were allowed in Islamic law because Islam doesn’t forbid helping and complementing each other to create a happy family. Being a TKW in fiqh muamalah contract is called Ijarah Amal and the wages from work are called Ujrah. Even though the implementation of work sometimes goes through work agreements, as long as it is still within reasonable limits and no one is harmed, the ijarah contract is still ongoing for overseas migrant workers. As long as their jobs were safe, they were permitted by their husbands or guardians, they were able to protect their honor and no one was wronged.